Multiple Myeloma: Challenges Encountered and Future Options for Better Treatment - Srijit Das; Norsham Juliana; Noor Anisah Abu Yazit; Sahar Azmani; Izuddin Fahmy Abu (MDPI, 2024)
Indexed by WOS/SCOPUS